Mobile Printer with Bluetooth Compatibility Using Raspberry PI (International Journal of Engineering and Computer Science, 2016)
This paper proposes a design of a device which directly prints the data stored inside the Mobile without the assistance of a desktop computer. The common data printing procedure has to use desktop computer as a relay medium, first receiving the data from mobile and then sending it to printer using an appropriate printing Method. This is rather cumbersome.The design compromises Raspberry pi having Debian flavor of Unix. The Common Unix Printing system installed on Raspberry Pi do the print job.